Project based learning model in digital literacy course in education to improve creativity of pgsd unja students in writing scientific articles - Eka Sastrawati; Maryono; Yantoro; Destrinelly (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This study aimed to improve students' creativity in writing scientific articles by applying the project-based Learning (PjBL) model. This type of research is classroom action research with four stages: planning, implementation, observation, and reflection. The research instrument used an observation sheet and a questionnaire for writing article creativity. Observations were carried out during learning, and a creativity questionnaire was given at the end of each cycle. Based on the study's results, it was obtained in cycle one that the indicator of fluent thinking creativity was 27% with a lesser category, cycle II 50% with a lesser category, and cycle II 75% with a good category. Then, the flexible thinking indicator in cycle 1 was 34% with a less category, cycle II 60% with a good category, and cycle III 71% with a good category. The original thinking indicator in cycle 1 was 28% with a less category, cycle II 62% with a good category, and cycle III 71% with a good category. The elaborative thinking indicator in cycle 1 was 33% with a less category, cycle II 63% with a good category, and cycle III 72% with a good category.